Novel Smooth Muscle Ca2+-Signaling Nanodomains in Blood Pressure Regulation. Issue 7 (27th June 2022) - Chen, Yen-Lin; Daneva, Zdravka; Kuppusamy, Maniselvan; Ottolini, Matteo; Baker, Thomas M.; Klimentova, Eliska; Shah, Soham A.; Sokolowski, Jennifer D.; Park, Min S.; Sonkusare, Swapnil K.
Abstract : Background: Ca 2+ signals in smooth muscle cells (SMCs) contribute to vascular resistance and control blood pressure. Increased vascular resistance in hypertension has been attributed to impaired SMC Ca 2+ signaling mechanisms. In this regard, transient receptor potential vanilloid 4 (TRPV4SMC ) ion channels are a crucial Ca 2+ entry pathway in SMCs. However, their role in blood pressure regulation has not been identified. Methods: We used SMC-specific TRPV4 −/− (TRPV4SMC −/− ) mice to assess the role of TRPV4SMC channels in blood pressure regulation. We determined the contribution of TRPV4SMC channels to the constrictor effect of α1 adrenergic receptor (α1AR) stimulation and elevated intraluminal pressure: 2 main physiologic stimuli that constrict resistance-sized arteries. The contribution of spatially separated TRPV4SMC channel subpopulations to elevated blood pressure in hypertension was evaluated in angiotensin II–infused mice and patients with hypertension. Results: We provide first evidence that TRPV4SMC channel activity elevates resting blood pressure in normal mice. α1AR stimulation activated TRPV4SMC channels through PKCα (protein kinase Cα) signaling, which contributed significantly to vasoconstriction and blood pressure elevation. Intraluminal pressure–induced TRPV4SMC channel activity opposed vasoconstriction through activation of Ca 2+ -sensitive K + (BK) channels, indicating functionally opposite pools of TRPV4SMC channels. Superresolution imaging of SMCs revealed spatially separated α1AR:TRPV4 and TRPV4:BK nanodomains in SMCs. These data suggest that spatially separated α1AR–TRPV4SMC and intraluminal pressure–TRPV4SMC –BK channel signaling have opposite effects on blood pressure, with α1AR–TRPV4SMC signaling dominating under resting conditions. Furthermore, in patients with hypertension and a mouse model of hypertension, constrictor α1AR–PKCα–TRPV4 signaling was upregulated, whereas dilator pressure–TRPV4–BK channel signaling was disrupted, thereby increasing vasoconstriction and elevating blood pressure. Conclusions: Our data identify novel smooth muscle Ca 2+ -signaling nanodomains that regulate blood pressure and demonstrate their impairment in hypertension.